Social networks of cultural programs in television of Ecuador [Redes sociales de los programas de cultura en la televisión de Ecuador] - Suing Ruiz, A. (2015)
The training content, educational, and cultural are of minimal presence in the broadcast television in Ecuador. The Organic Law of Communication and the presence of social networks that have led to the participation of the target audiences through the so-called 'cultural convergence' can have an impact on changing this reality. The research analyzes the social networks Facebook and Twitter programs educates Educa TV, Expresarte y Aprendamos, between August 2014 and January 2015. The cases studied, thanks to educational policies, constitute almost the totality of the learning content, educational and cultural television broadcast of the Ecuador. The purpose of the research is to establish whether the programs of culture of the television signal ecuadorian open considered the integration into social networks as a mechanism for connection with the audience. The hypothesis are: 1) the proportion of cultural programs in the ecuadorian tv is low but tends to increase, 2) social networks are little used in the dissemination and dialog with the audience, and 3) The impact of social networks in the hearings in minimum. The research concludes that the cultural contents are scarce of the total of the schedule, but tend to rise; social networks are little used in the connection with the audience of the cultural programs and the impact they can achieve is minimum. The audiences of the programs of culture are not empowered, not involved built collectively.